Clinical and cost outcomes following genomics‐informed treatment for advanced cancers. (21st June 2021) - Weymann, Deirdre; Pollard, Samantha; Chan, Brandon; Titmuss, Emma; Bohm, Alexandra; Laskin, Janessa; Jones, Steven J. M.; Pleasance, Erin; Nelson, Jessica; Fok, Alexandra; Lim, Howard; Karsan, Aly; et al.
Abstract: Background: Single‐arm trials are common in precision oncology. Owing to the lack of randomized counterfactual, resultant data are not amenable to comparative outcomes analyses. Difference‐in‐difference (DID) methods present an opportunity to generate causal estimates of time‐varying treatment outcomes. Using DID, our study estimates within‐cohort effects of genomics‐informed treatment versus standard care on clinical and cost outcomes. Methods: We focus on adults with advanced cancers enrolled in the single‐arm BC Cancer Personalized OncoGenomics program between 2012 and 2017. All individuals had a minimum of 1‐year follow up. Logistic regression explored baseline differences across patients who received a genomics‐informed treatment versus a standard care treatment after genomic sequencing. DID estimated the incremental effects of genomics‐informed treatment on time to treatment discontinuation (TTD), time to next treatment (TTNT), and costs. TTD and TTNT correlate with improved response and survival. Results: Our study cohort included 346 patients, of whom 140 (40%) received genomics‐informed treatment after sequencing and 206 (60%) received standard care treatment. No significant differences in baseline characteristics were detected across treatment groups. DID estimated that the incremental effect of genomics‐informed versus standard care treatment was 102 days (95% CI: 35, 167) on TTD, 91 days (95% CI: −9, 175) on TTNT, and CAD91, 098 (95% CI: 46, 848, 176, 598) on costs. Effects were most pronounced in gastrointestinal cancer patients. Conclusions: Genomics‐informed treatment had a statistically significant effect on TTD compared to standard care treatment, but at increased treatment costs. Within‐cohort evidence generated through this single‐arm study informs the early‐stage comparative effectiveness of precision oncology. Abstract : Difference‐in‐difference analysis is used to address confounding when analyzing real‐world data from a single‐arm precision oncology trial. Enrolled patients receiving genomics‐informed treatment are treated longer, suggesting improved efficacy, but at an increased cost compared to those receiving standard care.